Increasing adherence to plotting e-partograph: a quality improvement project in a rural maternity hospital in India. (3rd August 2021) - Jain, Shuchi; Kumar, Pramod; Jain, Manish; Bathla, Megha; Joshi, Shiv; Srivastava, Sushil; Singh, Mahtab; Sudke, Ajit; Datta, Vikram; Shivkumar, Poonam
Abstract : Abnormal prolonged labour and its effects are important contributors to maternal and perinatal mortality and morbidity worldwide. E-partograph is a modern tool for real-time computerised recording of labour data which improves maternal and neonatal outcome. The aim was to improve the rates of e-partograph plotting in all eligible women in the labour room from existing 30% to achieve 90% in 6 months through a quality improvement (QI) process. A team of nurses, obstetricians, postgraduates and a data entry operator did a root cause analysis to identify the possible reasons for the drop in e-partograph plotting to 30%. The team used process flow mapping and fish bone analysis. Various change ideas were tested through sequential Plan-Do-Study-Act (PDSA) cycles to address the issues identified. The interventions included training labour room staff, identification of eligible women and providing an additional computer and internet facility for plotting and assigning responsibility of plotting e-partographs. We implemented these interventions in five PDSA cycles and observed outcomes by using control charts. A set of process, output and outcome indicators were used to track if the changes made were leading to improvement. The rate of e-partograph plotting increased from 30% to 93% over the study period of 6 months from August 2018 to January 2019. The result has been sustained since the last PDSA cycle. The maternal outcome included a decrease in obstructed and prolonged labour with its associated complications from 6.2% to 2.4%. The neonatal outcomes included a decrease in admissions in the neonatal intensive care unit for birth asphyxia from 8% to 3.4%. It can thus be concluded that a QI approach can help in improving adherence to e-partography plotting resulting in improved maternal health services in a rural maternity hospital in India.